Fuels and Fuel Technology: A Summarized Manual in Two Volumes - Francis, Wilfrid; Thring, M. W; Jones, D. C. Rhys; Gaskell, T. F (Pergamon, 2016)
Fuels and Fuel Technology, Volume One: A Summarized Manual provides information pertinent to the fundamental aspects of fuels and fuel technology. This book presents a reasonably accurate summary of the existing knowledge and literature relating to fuel technology.Organized into two sections encompassing 72 data sheets, this volume begins with an overview of fuels as organic combustible substances used mainly or solely for the production of useful heat that are divided into three classes, namely, solid, liquid, and gaseous fuels. This text then examines the main chemical components of wood. This book discusses as well the commercial production of peat. The final section deals with the calculations of theoretical and actual air requirements, dry and wet flue gases, and carbon dioxide in flue gases.This book is a valuable resource for chemists and fuel technologists. Students who are interested to obtain a qualification in the subject of fuels or fuel technology will also find this book useful.